Equality and differences: group interaction in mixed focus groups of users and professionals discussing power. Issue 1 (1st January 2018) - Femdal, Ingrid; Solbjør, Marit
ABSTRACT: Using focus groups, the group interaction provide an important source of data about the group process. The aim of this study is to explore how users and professionals in mixed focus groups interact when discussing power in user-professional relationships. By analysing three mixed focus group discussions where both mental health service users and professionals participate, the article contributes to the discussion on focus group interaction in mixed focus groups. The analysis is inspired by Stevens' twelve-question guide for group interaction. The results show how the participants related to the vignettes, how they related to each other, and contradictions and disagreements in the focus groups discussing the vignettes. Despite the participant's background as users and professionals, the vignettes engaged the group discussions and became a tool for equality within the groups. By discussing power in user-professional relationships in mixed focus groups, the vignettes were interpreted from perspectives as user, mental health workers and researchers. Mixed focus group interaction can make a valuable contribution to developing knowledge in the field of mental health service research.